2016
DOI: 10.1007/s10792-016-0211-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens implantation without the use of ophthalmic viscosurgical device

Abstract: The purpose of this study was to determine whether single-piece hydrophilic acrylic intraocular lens can be safely implanted without the use of ophthalmic viscosurgical devices. This retrospective study comprised 100 eyes having phacoemulsification and intraocular lens implantation without the use of ophthalmic viscosurgical device. 80 eyes with the use of a viscosurgical device are used as control group. In this intraocular lens implantation technique, the anterior chamber was maintained with an irrigation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The cortical material was removed using an irrigation/aspiration probe. Following cortex removal, the hydroimplantation technique 11 was used to place the hydrophobic acrylic intraocular lens in the capsular bag using an injector system. Finally, the main and side-port incisions were closed, and endophthalmitis prophylaxis was performed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The cortical material was removed using an irrigation/aspiration probe. Following cortex removal, the hydroimplantation technique 11 was used to place the hydrophobic acrylic intraocular lens in the capsular bag using an injector system. Finally, the main and side-port incisions were closed, and endophthalmitis prophylaxis was performed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In high-risk patients, early postoperative IOP increase above 28 mmHg was reported in up to 46.4% of high-risk patients [9]. The risk factors for IOP spikes following PCS include residual viscoelastic material [13][14][15], resident-performed surgery [16][17][18], glaucoma [19,20], exfoliation syndrome [21], axial length of more than 25 mm [22], tamsulosin intake [23], and topical steroid application in steroid responders [24]. Postoperative anterior chamber inflammation might also result in an early IOP increase [25].…”
Section: Iop Spikesmentioning
confidence: 99%
“…The risk factors for IOP spikes following PEI include residual viscoelastic material [23,24] , residentperformed surgery [17,25,26] , glaucoma [14,16] , exfoliation syndrome [27] , an axial length of more than 25 mm [28] , and topical steroid application in steroid responders [29] . However, a few studies have reported the associations of IOP spike after PEI-GSL in PACG.…”
Section: Discussionmentioning
confidence: 99%